Working with limitations: social media management in local government on Solo region - Andre Rahmanto (Faculty of Communications Science, Dr. Soetomo University, 2024)
Government communication plays an important role in the two-way relationship between government and society. The development of social media platforms fulfills the information function for the government. The model of using social media is important in connection with the implementation of good governance in the administration of government. The method used in this research is qualitative. In particular, the researchers conducted an FGD (Focus Group Discussion) with the Solo Raya government to obtain information related to social media management. The result of this research is that social media is currently a platform that is often used by the government of the City of Solo Raya to provide information to the public. The function of social media is still minimal to 1) build program support and legitimacy, 2) identify and respond to community needs. 3) Define government services and provide government accountability mechanisms.